Operating Speed Based Alignment Consistency Evaluation Using Driving Simulator: Case Studies from Taigan Freeway in Jiangxi, China - Wang, Yonggang; Xu, Guomiao; Bai, Han (Promet - Traffic&Transportation, 2013)
Geometric design consistency refers to the conformance of a proposed or existing freeway’s geometry with the driver’s expectancy. Considerable efforts have been undertaken to develop potential quantitative consistency measures and models to estimate them. However, little work has been focused on the facts of freeways in China, especially in mountainous areas. The primary objective of this study is to examine and quantify the design consistency of a freeway, using an interactive driving simulator, so as to identify any inconsistency on the roadway geometry and improve its overall safety performance. More specifically, the techniques to evaluate the consistency of a geometric design depend on three criteria: design consistency, operating speed consistency, and consistency in driving dynamics, as well as three levels of consistency: good, acceptable and poor. In the case of Taigan Freeway, a part of G45 Daguang Freeway in Jiangxi, China, a 21km long segment has been divided into 38 sections including 22 curves and 16 tangents, and transferred into the graphics models in the simulator system. There were 42 drivers required to take part in the simulation experiment and the speed, location of vehicle, and other real time data were recorded as well. The findings have shown that these proposed measures and standards can identify a geometric inconsistency more effectively when there is a large rate of change in the alignment elements for a successive roadway segment.